Linguistic Analysis On Slogan Of Mobile Phone On Pulsa Magazine - Faisal, Andi Rois Al; , Prof. Dr. Endang Fauziati, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research studies on slogan of mobile phone on Pulsa magazine. The objectives of the study are to explain the types of slogan, the linguistic forms, the function of slogan, and the meaning of the slogans. This research applies descriptive qualitative research. By applying this method, the researcher uses Pulsa magazine which contains English slogan as the data source, while the data of the research can be word, phrase, and sentence of slogan used in advertisement of mobile phone product in Pulsa magazine. The method of collecting data is documentation method, collected Pulsa magazine, choose slogan English, and documented the English slogans with the way make the list of English-language slogans. The technique of analysis applied in this study is descriptive interpretative. The results of this study are, first, the types of the slogans are in the type descriptive slogans, superlative slogans, imperative slogans, and provocative slogans. Second, the linguistic form of mobile phone slogans are in the form of word (adjective, verb, and noun), phrase (noun phrase), and sentence (declarative sentence and imperative sentence). Third, the language function mobile phone slogans are representational function, imaginative function, heuristic function, and personal function. Fourth, the meanings of mobile phone slogans are affective meaning and connotative meaning.